P 89 Evaluating correlations of muscle MRI derived fat fractions of leg muscles and clinical outcome measurements in patients with LGMD2A. (May 2022) - Forsting, J.; Rohm, M.; Rehmann, R.; Güttsches, A.K.; Froeling, M.; Tegenthoff, M.; Vorgerd, M.; Schlaffke, L.
Abstract : 1. Introduction: Quantitative MRI (qMRI) techniques like Dixon fat fraction (FF) are a promising non-invasive tool in the evaluation of neuromuscular diseases [1]. Increase of FF has been shown to precede clinical deterioration of muscle function in different longitudinal studies [2]. In this study we aimed to analyse Dixon fat fraction of calf and thigh muscles in a cohort of patients with genetically confirmed LGMD Type 2A and to correlate the quantitative values FF with clinical findings and daily life activities assessed by questionnaires. 2. Methods: In total, 19 individuals with genetically confirmed LGMD2A (10 females, mean age 39.8 ± 13.4 years) and 19 age- and gender-matched healthy volunteers (10 females, mean age 39.2 ± 12.6 years) participated in this study. Clinical assessments included Quick Motor Function Measure (QMFM), the 6-Minute Walk Test (6-MWT), time to walk 10 meters (T10m) and timed up- and-go test (TUG) and the assessments of daily life activities by the ACTIVLIM and the Neuromuscular Symptom Score [3]. All participants underwent a 3T MRI acquiring Dixon sequences of both legs. Fat fractions of quadriceps, hamstrings, dorsi extensors and plantar flexors were calculated. Pearson and Spearman rank correlation coefficients were calculated between FF and clinical outcome measurements in both groups and daily life activities in LGMD group. 3. Results: We found significant moderate to strong correlations between FF and gait measurements for all muscle groups (r ≥ 0.646, p < 0.001) and moderate to high correlation of daily activities and FF (r ≥ 0.550, p < 0.001). An ANOVA revealed significant differences of FF between LGMD and healthy control group (Main Effect: p < 0.001). 4. Discussion: Advanced qMRI techniques like Dixon FF can offer quantitative information about fat infiltration and inflammation. In this study FF in all muscle groups correlated strongly with clinical findings. Those findings are in line with the results of a previous study by Arrigoni in thigh muscles [4]. We conclude that Dixon fat fraction should be considered a non-invasive biomarker in LGMD2A. 5. Citations: [1] Aivazoglou LU et al. MR imaging of inherited myopathies: a review and proposal of imaging algorithms. Eur Radiol. Epub 21/04/2021. doi:10.1007/s00330-021-07931-9. [2] Burakiewicz J et al. Quantifying fat replacement of muscle by quantitative MRI in muscular dystrophy. J Neurol. 2017; 264(10):2053-2067. doi:10.1007/s00415-017-8547-3. [3] Vandervelde L et al. ACTIVLIM: A Rasch-built measure of activity limitations in children and adults with neuromuscular disorders. Neuromuscul Disord . 2007;17(6):459-469. doi:10.1016/j.nmd.2007.02.013. [4] Arrigoni F et al. Multiparametric qMRI assessment of thigh muscles in LGMD 2A and 2B. Muscle and Nerve . 2018;58(4):550-558. doi:10.1002/mus.26189.